Effects of Igneous Intrusion on Microporosity and Gas Adsorption Capacity of Coals in the Haizi Mine, China - Jingyu Jiang; Yuanping Cheng (The Scientific World Journal)
This paper describes the effects of igneous intrusions on pore structure and adsorption capacity of the Permian coals in the Huaibei Coalfield, China. Twelve coal samples were obtained at different distances from a ~120 m extremely thick sill. Comparisons were made between unaltered and heat-affected coals using geochemical data, pore-fracture characteristics, and adsorption properties. Thermal alteration occurs down to ~1.3 × sill thickness. Approaching the sill, the vitrinite reflectance (Ro) increased from 2.30% to 2.78%, forming devolatilization vacuoles and a fine mosaic texture. Volatile matter (VM) decreased from 17.6% to 10.0% and the moisture decreased from 3.0% to 1.6%. With decreasing distance to the sill, the micropore volumes initially increased from 0.0054 cm3/g to a maximum of 0.0146 cm3/g and then decreased to 0.0079 cm3/g. The results show that the thermal evolution of the sill obviously changed the coal geochemistry and increased the micropore volume and adsorption capacity of heat-affected coal (60–160 m from the sill) compared with the unaltered coals. The trap effect of the sill prevented the high-pressure gas from being released, forming gas pocket. Mining activities near the sill created a low pressure zone leading to the rapid accumulation of methane and gas outbursts in the Haizi Mine.